Do Antidepressants Worsen COPD Outcomes in Depressed Patients with COPD? - Alan G. Kaplan (Pulmonary Therapy)
Abstract The coexistence of depression with chronic obstructive pulmonary disease (COPD) has been associated with poorer outcomes. Studies have questioned the safety of antidepressants in patients with COPD. This review shows the potential relationships and the possible mechanisms and gives us good warnings on how to approach this problem. Treatment should be both non-pharmacological and pharmacological, but importantly tailored to the individual patient.